INTERNALIZATION OF ISLAMIC RELIGIOUS CHARACTER VALUES IN MADRASAH IBTIDAIYAH - Amin Ary; Maragustam Siregar; Mufrod Teguh Mulyo (Universitas Majalengka, 2023)
The internalization of Islamic religious character refers to the process by which individuals deeply and sincerely adopt the core principles, values, and moral guidelines of Islam into their personal beliefs, attitudes, and behaviors. This study aims to describe the internalization of Islamic religious Character values in Madrasah Ibtidaiyah Nurul Huda, Gondang, Sragen. This madrasah uses the concept of Aswaja An-Nahdliyah in academic and non-academic activities. This concept is interesting to be described in more depth. This type of research is using qualitative and described analysis using phenomenological and naturalistic approaches. Data collection techniques are interview and observation. The data analysis method used is qualitatively descriptive. The results of this study show that the internalization of a character building in the institution can be divided into two important subjects. Firstly, direct internalization through Aswaja course. Secondly indirect internalization, namely by internalizing aswaja values with the principles of tawasut or moderate, tasamuh or tolerance, tawazun or balanced, i'tidal or impartial and amar ma'ruf nahi munkar. In addition, the madrasah is categorized as having understood the philosophical meaning, moral message, good advice contained in the character values of Aswaja An-Nahdliyah; having reconstructed the internalization of aswaja an-Nahdliyah character values in a way; introducing, familiarizing, instilling, the importance of aswaja An-Nahdliyah character values, and becoming an option in the development of noble character in line with the values of Islamic teachings to welcome a strong millennial generation in accordance with the expectations of Islamic religion and Indonesian country. Penelitian ini bertujuan untuk mendeskripsikan internalisasi nilai karakter agama Islami di Madrasah Ibtidaiyah Nurul Huda, Gondang, Sragen. Madrasah ini menggunakan konsep Aswaja An-Nahdliyah dalam kegiatan akademik maupun non akademik. Konsep ini menarik untuk dipaparkan lebih dalam. Jenis penelitian ini menggunakan analisis kualitatif dan deskriptif dengan pendekatan fenomenologis dan naturalistik. Teknik pengumpulan data adalah wawancara and observasi. Metode analisis data yang digunakan adalah deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa internalisasi pembentukan karakter di lembaga dapat dibagi menjadi dua mata pelajaran penting. Pertama, internalisasi langsung melalui kursus Aswaja. Baik internalisasi tidak langsung yaitu dengan menginternalisasi nilai-nilai aswaja dengan prinsip tawasut atau moderat, tasamuh atau toleransi, tawazun atau seimbang, i'tidal atau tidak memihak dan amar ma'ruf nahi munkar. Selain itu, madrasah dikategorikan telah memahami makna filosofis, pesan moral, nasehat baik yang terkandung dalam nilai-nilai karakter Aswaja An-Nahdliyah; telah merekonstruksi internalisasi nilai-nilai karakter aswaja an-Nahdliyah dengan cara; mengenalkan, membiasakan, menanamkan, pentingnya nilai-nilai karakter aswaja An-Nahdliyah, dan menjadi pilihan dalam pengembangan akhlak mulia yang sejalan dengan nilai-nilai ajaran Islam untuk menyongsong generasi milenial yang tangguh sesuai dengan harapan agama Islam dan negara Indonesia.